DDAH1/ADMA Regulates Adiponectin Resistance in Cerebral Ischemia via the ROS/FOXO1/APR1 Pathway. (25th April 2022) - Zhao, Yichen; Zhang, Minjie; Dou, Yunxiao; Du, Kangshuai; Liu, Xueyuan; Zhao, Yanxin
Abstract : Dimethylarginine dimethylaminohydrolase 1 (DDAH1) protects against cerebral ischemia injury via regulating the level of asymmetric dimethylarginine (ADMA). This study is aimed at exploring the effect of adiponectin resistance on ADMA-induced neuronal loss in ischemic stroke (IS) and the underlying mechanism. DDAH1 knockout (DDAH1 -/- ) and wild-type (DDAH1 +/+ ) rats underwent middle cerebral artery occlusion/reperfusion (MCAO/R). Plasma and brain adiponectin levels and the expressions of adiponectin receptor 1 (APR1), adaptor protein, phosphotyrosine interacting with PH domain and leucine zipper 1 (APPL1), adenosine monophosphate-activated protein kinase (AMPK), and phosphorylated AMPK were determined after 24 h, 3 days, and 7 days. Neurological behavior, infarct volume, and adiponectin signaling were evaluated using adiponectin peptide or AdipoRon. The levels of reactive oxygen species (ROS) and Forkhead box O1 (FOXO1) (a transcription factor for APR1) were also assessed. An oxygen-glucose deprivation/reoxygenation (OGD/R) model was established in primary neurons. DDAH1 was overexpressed in neurons, after which FOXO1 expression, ROS production, adiponectin resistance, and cell viability were detected. DDAH1 -/- rats showed no significant difference in adiponectin level in either plasma or brain after MCAO/R in DDAH1 +/+ rats, but downregulated APR1 expression and suppressed adiponectin signaling were observed. AdipoRon, but not adiponectin peptide, attenuated the neurological deficits and adiponectin resistance in DDAH1 -/- rats. ROS accumulation and phosphorylated FOXO1 expression also increased with DDAH1 depletion. Following DDAH1 overexpression, decreased cell viability and inhibited adiponectin signaling induced by OGD/R were alleviated in primary neurons, accompanied by reduced ROS production and phosphorylated FOXO1 expression. Our study elucidated that in IS, DDAH1 protected against adiponectin resistance in IS via the ROS/FOXO1/APR1 pathway.